Inhibin B and antiMüllerian hormone as surrogate markers of fertility in male and female Crohn’s disease patients: a case-control study - Gutiérrez, Ana; Muñoz-Pérez, Roser; Zapater, Pedro; Mira, Cristina; Rodríguez, Andrés; Sempere-Robles, Laura; Torregrosa, María Eugenia; Alfayate, Rocio; Moreno-Torres, Violeta; Bernal, Lorena; Belén-Galipienso, Olivia; Cameo, Jose Ignacio; et al. (Frontiers in Medicine, 2024)
Background Several studies suggest that women with Crohn disease (CD) have reduced fertility due to decreased ovarian reserve, among other causes. On the other hand, male CD patients could have difficulties conceiving. The present study aimed to test the effect of CD on both male and female fertility potential, Sertoli cell function and ovarian reserve, assessed by inhibin-B (IB) plus IB:FSH ratio (IFR) and antiMüllerian hormone (AMH), respectively. Sexual dysfunction (SD) was studied as secondary endpoint. Methods We performed a cross-sectional, case–control study. Serum IB levels plus IFR were measured in 58 men with CD and compared to 25 age-matched healthy controls (HC). Serum AMH levels were measured in 50 women with CD and in 30 HC matched by age. SD was assessed by means of the International Index of Erectile Function (IIFE-15) in males and the Index of Female Sexual Function (IFSF) in women. Results A total of 108 CD patients and 55 HC were included. IB serum levels were significantly lower in CD men than in HC (177 ± 58 vs. 234 ± 75 pg./mL, p = 0.001). IFR was also decreased in CD patients compared to HC (58.27 ± 59.5 vs. 91.35 ± 60.04, p = 0.014). Women with CD > 30 years had lower serum AMH levels compared to HC (1.15 ± 0.74 vs. 2.14 ± 1.68 ng/mL, p = 0.033). In addition, CD women >30 years presented a serum AMH < 2 ng/mL more frequently than HC (90% vs. 40%, p = 0.004). The prevalence of SD was significantly higher among both male and female CD patients compared to HC, without association to fertility potential. Age was the only predictor of low ovarian reserve. Conclusion Testicular Sertoli cell function assessed through serum IB levels and IFR is decreased in CD male patients compared to HC, regardless of age. Age > 30 years is the single independent predictor of reduced ovarian reserve in women with CD. These results should be confirmed in further studies in order to properly counsel patients with CD and desire for offspring.